FINANCIAL REPORTING OF COMPREHENSIVE INCOME IN THE FOOD AND BEVERAGE SECTOR IN THE REPUBLIC OF SERBIA - Obradović, Vladimir; Karapavlović, Nemanja (Economics of Agriculture, 2017)
The paper discusses financial reporting of comprehensive income of companies in the food and beverage sector in the Republic of Serbia. The aim of the research is to examine whether the introduction of the concept of net comprehensive income has brought significant information for users of financial statements. The analysis has been conducted on a sample of 132 companies from the mentioned sector on the basis of financial statements for 2014. We find that there is very high positive correlation between net income and net comprehensive income; that there is no statistically significant difference between net income and net comprehensive income; that there is no statistically significant difference between the return on equity calculated by using net income and the return on equity calculated by using net comprehensive income; and that net comprehensive income is more volatile in time than net income.